Teacher Teaching Styles and Student Learning Motivation in Economics Education: Evidence from Senior High School Classrooms - Lutfia Adelia; Muhammad Yany; Sahiruddin (Yayasan Ahmar Cendekia Indonesia, 2026)
This study aimed to examine the influence of teachers’ teaching style on students’ learning motivation in Economics among Grade X students at SMA Negeri 20 Bone. This research employed a quantitative approach using an ex post facto design. The sample consisted of 32 students selected through purposive sampling. Data were collected using questionnaires and documentation. The collected data were analyzed using descriptive statistics and simple linear regression analysis with the assistance of SPSS version 26. The findings revealed that teachers’ teaching style had a significant positive influence on students’ learning motivation in Economics. The simple linear regression analysis produced the equation Y = 19.145 + 0.550X, indicating that every one-unit increase in teachers’ teaching style score increased students’ learning motivation by 0.550 units. The significance value of 0.001, which was lower than the 0.05 significance level, confirmed that the effect was statistically significant. These findings indicate that improving teachers’ teaching style can enhance students’ learning motivation in Economics among Grade X students at SMA Negeri 20 Bone.